Blood and belief : the PKK and the Kurdish fight for independence. - Marcus, Aliza (NYU Press, 2007)
The Kurds, who number some 28 million people in the Middle East, have no country they can call their own. Long ignored by the West, Kurds are now highly visible actors on the world's political stage. More than half live in Turkey, where the Kurdish struggle has gained new strength and attention since the U.S. overthrow of Saddam Hussein in neighboring Iraq. Essential to understanding modern-day Kurds--and their continuing demands for an independent state--is understanding the PKK, the Kurdistan Workers' Party. A guerilla force that was founded in 1978 by a small group of ex-Turkish university st.